Introduction to Journal of South American Earth Sciences special issue on “Magmatism of southernmost South America” - Navarrete Granzotto, César Rodrigo (2021)
complex magmatic history due to the occurrence of multiple large-scalegeological processes that include mantle plumes impingements, slabwindows opening, collisional episodes, normal and flat subductionevents, mantle transition zone-derived melts ascent, slab break-offevents, etc. (e.g., Mpodozis and Kay, 1992; Gorring et al., 1997; Rileyet al., 2001; Pankhurst et al., 2006; Kay et al., 2007; Ramos, 2008;Breitsprecher and Thorkerlson, 2009; Arag´on et al., 2013; Gianni et al.,2018; Navarrete et al., 2019; 2020; Iannelli et al., 2020). Although thismagmatic history began during the Neoproterozoic, the igneous activityof the last 300 Myr has been remarkably intense and voluminous,constituting one of the most distinctive geological features of this region.So much so that three Phanerozoic Large Igneous Provinces (LIPs) havebeen proposed (Kay et al., 1989; Pankhurst et al., 1998; Kay et al., 2007;Bastías-Mercado et al., 2020 ? this special issue). The first of them linkedto the Permian-Triassic subduction events (Choiyoi SLIP - Bastías-Mercado et al. this especial issue, and references therein; Oliveroset al., 2019), although there are also proposals that have suggested anorigin related to slab-breakoff episodes (e.g., Mpodozis and Kay, 1992;Pankhurst et al., 2006). The second would have been generated by theJurassic Karoo mantle plume impingement added to the paleo-pacificsubduction during the beginning of the Gondwana breakup (ChonAike SLIP - e.g., Kay et al., 1989; Pankhurst et al., 1998), whereas theorigin of the Oligocene-Miocene third province (Somuncura LIP ? Kayet al., 2007) is still under discussion. There are proposals that invoke amantle plume impingement (Kay et al., 2007), a lithospheric delaminationevent (Remesal et al., 2012), as well as the mantle transitionzone-derived melts ascent due to the Farallon slab stagnation (Navarreteet al., 2020), between others. In this special issue, most of the articles arelinked to these Permian-Triassic, Jurassic and mid-Cenozoic LIPs(Fig. 1), although multiple subduction-related magmatic events are alsoincluded, such as the formation of the Patagonian Batholith (e.g., Pankhurstet al., 1999) and the eruption of the volcanic products linked tothe magmatism of the Andean subduction zone (e.g., Rapela et al., 1984;1988).From the economic point of view, the socio-economic developmentof Chile and Argentina was marked by the magmatism of the southernmostSouth American region. In this sense, the Jurassic magmatismof Patagonia gave rise to numerous precious metals hydro-thermal largemineral deposits (e.g., Schalamuk et al., 1997; Echavarría et al., 2005;Guido and Campbell, 2011; Permuy Vidal et al., 2016; Tassara et al.,2017), whereas the Cenozoic intraplate magmatism of Patagoniafavored the hydrocarbon maturation in Patagonian oil and gas producingMesozoic basins (e.g., Rodriguez and Littke, 2001; Spacapan et al.,2018). Also, giant porphyry copper deposits were produced by theMeso-Cenozoic subduction-related magmatism in the Andean region (e.g., Mpodozis and Cornejo, 2012; Lee and Tang, 2020).Therefore, new contributions that improve the comprehension of thelarge magmatic episodes of southernmost South America are highlyrelevant for the general geological knowledge of this region, and theirinterest exceeds that of the academic geological community.